2014
DOI: 10.1558/sols.v8i1.139
|View full text |Cite
|
Sign up to set email alerts
|

Miami-Cuban Spanish vowels in contact

Abstract: While traditional studies on Spanish vowels have agreed that it is a stable system with very little variation, Varela (1992) claims to have observed English transfer phenomena in the vowel system of Miami Cuban Spanish (i.e. schwa in unstressed position, diphthongization of mid-vowels, and the use of English vowels in place of Spanish vowels: e.g. [æ] for /o/, [æk.tú.b?e] for octubre). The current study empirically tests Varela’s claims of English transfer in the Spanish vowel system of three generations of Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Although cross-dialectal comparisons have revealed some minor quality and quantity differences (Chládková et al, 2011, Quilis & Esgueva, 1983, research examining bilinguals -both L2 learners of Spanish and HSs -suggests substantial variation in distribution and organization. One of the most salient differences concerns the position of /u/, which is often fronted (i.e., higher F2) in bilingual speech relative to monolingual norms (Alvord & Rogers, 2014;Cobb & Simonet, 2015;Grijalva, Piccinini, & Arvaniti, 2009;Menke & Face, 2010;Ronquest, 2012;Willis, 2005; among others). With specific reference to HSs, Ronquest (2012) found that /e/ was produced farther back in the acoustic space than traditionally depicted, and that the back vowel space was much more condensed relative to the front vowel space.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cross-dialectal comparisons have revealed some minor quality and quantity differences (Chládková et al, 2011, Quilis & Esgueva, 1983, research examining bilinguals -both L2 learners of Spanish and HSs -suggests substantial variation in distribution and organization. One of the most salient differences concerns the position of /u/, which is often fronted (i.e., higher F2) in bilingual speech relative to monolingual norms (Alvord & Rogers, 2014;Cobb & Simonet, 2015;Grijalva, Piccinini, & Arvaniti, 2009;Menke & Face, 2010;Ronquest, 2012;Willis, 2005; among others). With specific reference to HSs, Ronquest (2012) found that /e/ was produced farther back in the acoustic space than traditionally depicted, and that the back vowel space was much more condensed relative to the front vowel space.…”
Section: Previous Researchmentioning
confidence: 99%
“…What is needed is inquiry that compares a large number of diverse variables." Following Thomas's suggestion, this study includes analyses of four distinct variables that are known to vary based on speakers' linguistic experience (i.e., bilingual versus monolingual), as well as across dialects: realization of intervocalic /bdg/ (Carrasco, Hualde, & Simonet, 2012;Rao, 2015), Spanish vowels (Alvord & Rogers, 2014;Chládková, Escudero, & Boersma, 2011), prosodic rhythm (Shousterman, 2014;Carter & Wolford, 2016), and bilingual discourse markers (Torres, 2002(Torres, , 2011Torres & Potowski, 2008). Examining linguistic variation through multiple variables simultaneously allows for the formation of a more nuanced and complete understanding of the structure and trajectory of Spanish in the region.…”
Section: Introductionmentioning
confidence: 99%
“…The vowels that seem to undergo the greatest modification when compared to those of native speakers are the high vowels /iu/ (especially /u/) and the mid vowels /eo/. While one could surmise that the observed reduction is due to contact with English, Alvord and Rogers (2014) present Cuban data in which both HL users and older immigrants exhibit this trend.…”
Section: Vowelsmentioning
confidence: 58%
“…Studies delving into the Spanish vowel system of HL users find vowel spaces that are not as symmetrical as those of native speakers and that do display evidence of shift toward the center of the vowel space (i.e., reduction) in unstressed syllables (Alvord & Rogers, 2014;Boomershine, 2012;Ronquest 2012Ronquest , 2013Willis, 2005). Both of these trends are particularly noteworthy in more spontaneous speech styles.…”
Section: Vowelsmentioning
confidence: 99%
“…For instance, Einfeldt et al (2019) found that heritage speakers of Italian maintain the contrast between singleton and geminate consonants. However, in other areas they show variability that is different from monolingual norms (Alvord & Rogers, 2014; Amengual, 2016; Colantoni et al, 2016; Godson, 2004; Henriksen, 2015; Robles-Puente, 2014; Ronquest, 2012, 2013). Studies have found that heritage language vowel space either shows assimilation to or dissimilation from that of the majority language (Cummings Ruiz, 2019; Ronquest, 2012, 2013) and that heritage language stop productions are affected by factors such as cognate status (Amengual, 2012), code-switching (Łyskawa, Maddeaux, Melara & Nagy, 2016), and speaker generation (Mayr & Siddika, 2018; Nodari, Celata & Nagy, 2019).…”
Section: Understanding Heritage Phonological Grammarsmentioning
confidence: 93%